"Common Ground": East Coast Meets West Coast on Zoom. Issue 4 (26th November 2021) - Levey, Jessie; Mansbridge, Anna
Abstract: "Common Ground" connects two youth dance companies from opposite ends of the United States: Barefoot Dance Company from West Park, NY, and Kaleidoscope Dance Company from Seattle, WA. The goal of the project was to give students an opportunity to choreograph together despite their physical distance. During four rehearsals on Zoom in January 2021, the dancers created short gesture phrases based on something they had in common, and a shape sequence using stick figure drawings inspired by choreographer Remy Charlip's Air Mail Dances. Combining material filmed individually and on Zoom, we created a dance film that celebrates the unique opportunities available to us online during the COVID-19 pandemic. We hope this experience will inspire other educators to reach out to colleagues worldwide and form new partnerships leading to the development of collaborative student work.